Biomass-glycerol briquettes are not necessarily mechanically stable and energetically effective - Moreira, Bruno Rafael de Almeida [UNESP]; Viana, Ronaldo da Silva [UNESP]; Moreira, Samuel Dias [UNESP]; Lima, Monique dos Santos [UNESP]; Magalhães, Anderson Chagas [UNESP]; Miasaki, Celso Tadao [UNESP]; Caraschi, José Claudio [UNESP] (Springer Nature, 2020)
The re-use of glycerol from biodiesel industry as an alternative lubricant for making high-performance briquettes is usual. However, the technical performance of this agro-industrial residue is not consistent. This study outlines, accordingly, the real risk of introducing glycerol into the co-briquetting of highly caloric by-products of energy-crops. The production of hybrid briquettes consisted of pressing mixtures of residues of sugarcane and sorghum with the liquid additive at 10, 20, and 30 wt.% in bench-scale hydraulic piston presser machine. Irrespective of the blend, briquettes containing the supplement at the highest level as part of their composition ended up being much more hygroscopic (20.10%) and less energetic (3.15 GJ m−3). The explanation for the negative impact of glycerol on the thermomechanical behavior of briquettes would be overconcentration of additive capable of effectively defying compacting biomass. The degree of compaction during co-briquetting has likely gone down quickly with a maximizing level of glycerol. As long as the additive is not able to lubricate the feedstock suitably, improbability of biomass particles to successfully bond together to form themselves into mechanically stable and energetically effective briquettes is large. Besides lower density (273.80 kg m−3) and higher relaxation (22.75%), briquettes with glycerol at 30 wt.% generally were aesthetically unpleasing. Practically, these products resisted no longer to handling, transportation, and storage. They lost their shape easily during emptying and shifting them, thus, releasing larger quantities of biomass to the environment. Preliminary evidence of high-viscosity glycerol capable of limiting safe and effective production of high-performance briquettes for heating and power exists.
Keywords: Additive; Agro-residues; Biosolids; Densification; Waste-to-energy